Respuesta :

I hope this helps you
Ver imagen Аноним

Answer:

[tex]d(x)^{-1}= \frac{x+6}{-2}[/tex].

Step-by-step explanation:

Given :  d(x ) = -2x - 6.

To find : What is the inverse function .

Solution : We have given that  d(x ) = -2x - 6.

Step 1 : d(x) = y

Step 2) : Inter change y and x .

x = -2y -6.

Step 3) solve for y.

On adding both side by 6.

x + 6  = -2y.

On dividing by -2 both side.

[tex]\frac{x+ 6}{-2}[/tex] = y .

[tex]y = d(x)^{-1}[/tex]  is inverse of d(x).

Therefore, [tex]d(x)^{-1}= \frac{x+6}{-2}[/tex].